Exploring Pre-Service Teachers' Perceptions on Mental Health: An Initial Survey - Hamsu Kadriyan; Gunawan Gunawan; Ni Made Yeni Suranti; Dian Puspita Sari; Baik Nilawati Astini; Cut Warnaini (Indonesian Publication Center, 2026)
Mental health is a crucial aspect in shaping the professional readiness of prospective teachers. However, this issue remains underexplored in teacher education, despite the complex emotional and academic pressures faced by students. This study aims to describe the perceptions of prospective teachers regarding mental health, in terms of their knowledge, experiences, and expectations for institutional support. The research employed a descriptive quantitative approach involving 630 prospective teachers from various semesters. The instruments used consisted of a Likert scale, binary (Yes/No) questions, and open-ended questions. Data were analyzed using descriptive techniques, including mean scores, frequency distribution, and thematic analysis. The findings revealed that students demonstrated a high level of awareness regarding the importance of mental health (mean score = 4.85), yet not all felt comfortable discussing the issue or seeking help when experiencing psychological pressure. A total of 63.17% of respondents had experienced or knew someone who experienced mental health problems, but only 37.14% felt they had adequate resources to cope. Student suggestions included the need for mental health education, counseling services, and awareness campaigns within the campus environment. These findings underscore the importance of integrating mental health education into teacher training curricula. Systematic efforts are needed to enhance literacy, reduce stigma, and foster a more supportive campus environment for the psychological well-being of future educators.